The occurrence of the rumen ciliate Metadinium banksi Dehority, 1985 (Ophryoscolecidae, Entodiniomorphida) from domestic goats (Capra hircus L.) in Southeastern Turkey - Burk A. Dehority; Bayram Göçmen; Samiye Rastgeldi (2002)
Metadinium banksi was observed in rumen contents from a single goat out of eight living in southeastern Turkey. It constituted 0.25% of the total ciliate population and had a 12.5% frequency of appearance. The size and percentage occurrence of this species in the present study are compared to those previously reported for other animal hosts living in different geographical locations. This study reports for the first time in Turkey the presence of Metadinium banksi in arctic ruminants. Türkiye'nin güneydoğusunda yaşayan sekiz evcil keçiden birinin işkembe içeriğinde Metadinium banksi gözlenmiştir. Toplam işkembe siliyat faunasynyn %0.25'ini oluşturan bu siliyat keçilerimizde .5'lik bir görülme sıklığına sahiptir. Bu çalışmada belirlenen vücut ölçümleri ve bulunma yüzdesi, diğer coğrafi bölgelerde yaşayan farklı konaklardan rapor edilen değerlerle karşılaştırılmıştır. Bu çalışma Metadinium banksi'nin Türkiye'de arktik ruminantlarda bulunduğuna ilişkin ilk kayıttır.